2018
DOI: 10.1016/j.optom.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Cirrus HD-OCT and Topcon SP-3000P for measuring central corneal thickness

Abstract: PurposeTo compare and analyze the interchangeability of three measuring systems, each based on a different technique, for central corneal thickness (CCT) analysis.MethodsCCT measurements were measured using optical coherence tomography (OCT), non-contact specular microscopy (NCSM), and ultrasonic pachymetry (USP) in 60 eyes of 60 healthy patients with a mean age of 66.5 ± 15.0 years and a mean spherical equivalent of 0.43 ± 1.14 D. Analysis of variations in measurement concordance and correlation among the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(61 reference statements)
0
5
1
1
Order By: Relevance
“…In spite of the different protocols followed in each study (10,13,14), most have found a high resolution between the analyzed devices, as in the present study. This high correlation between devices was also reported by other authors, such as Cevik et al (11), who compared ultrasonic pachymetry and specular biomicroscopy.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…In spite of the different protocols followed in each study (10,13,14), most have found a high resolution between the analyzed devices, as in the present study. This high correlation between devices was also reported by other authors, such as Cevik et al (11), who compared ultrasonic pachymetry and specular biomicroscopy.…”
Section: Discussioncontrasting
confidence: 50%
“…Weiser et al (15) and Calvo et al (10) have reported that OCT and contact ultrasonic pachymetry provide similar values. On the other hand, and in contrast with our results, De Bernardo (13) and Fujioka (14) found slightly lower pachymetric values with the specular microscope compared to the Pentacam topography.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We read with great interest the article by Calvo-Sanz et al comparing specular microscopy (SM) with OCT and ultrasound pachymetry (USP). 1 …”
mentioning
confidence: 99%
“…Los valores de la paquimetría corneal obtenida mediante MENC son habitualmente menores que los determinados mediante ultrasonidos 73,[229][230][231] . Este dato puede que influya en los resultados, ya que la diferencia en el valor de la medición, puede hacer que un valor límite en el caso de la determinación mediante ultrasonidos, se convierta en estadisticamente significativo en la visita inicial.…”
Section: D2 Parámetros Funcionales Indirectos Del Endotelio Cornealunclassified